Control of Perovskite Crystal Growth by Methylammonium Lead Chloride Templating. Issue 8 (1st March 2016) - Binek, Andreas; Grill, Irene; Huber, Niklas; Peters, Kristina; Hufnagel, Alexander G.; Handloser, Matthias; Docampo, Pablo; Hartschuh, Achim; Bein, Thomas
Abstract: State‐of‐the‐art solar cells based on methylammonium lead iodide (MAPbI3 ) now reach efficiencies over 20 %. This fast improvement was possible with intensive research in perovskite processing. In particular, chloride‐based precursors are known to have a positive influence on the crystallization of the perovskite. Here, we used a combination of in‐situ X‐ray diffraction and charge‐transport measurements to understand the influence of chloride during perovskite crystallization in planar heterojunction solar cells. We show that MAPbCl3 crystallizes directly after the deposition of the starting solution and acts as a template for the formation of MAPbI3 . Additionally, we show that the charge‐carrier mobility doubles by extending the time for the template formation. Our results give a deeper understanding of the influence of chloride in the synthesis of MAPbI3 and illustrate the importance of carefully controlling crystallization for reproducible, high‐efficiency solar cells. Abstract : Act now ! The influence of chloride during the perovskite crystallization in planar heterojunction solar cells was investigated. It is shown that MAPbCl3 crystallizes directly after the deposition of the starting solution and acts as a template for the formation of MAPbI3 . The figure shows the schematic architecture of a perovskite solar cell prepared via the slow solvent evaporation technique based on PbCl2 .